Corrigendum: Severe and enduring' stage in anorexia nervosa: comparing eating attitudes, impairment and associated psychopathology(Front. Nutr., (2022), 9, (867401), 10.3389/fnut.2022.867401) - Ramos, Rita (2023)
In the published article, there was an error in the Funding statement. The funding statement for Eva Conceição was incorrectly displayed as “IF/01219/2014”. The correct Funding statement appears below.